ANALISIS PELAYANAN PROSES PEMBERIAN KREDIT PADA PD. BANK PERKREDITAN RAKYAT ROKAN HILIR CABANG KUBU KABUPATEN ROKAN HILIR - M Rojali; Indra Safri (UIR Press, 2015)
Local Companies Rokan Hilir Rural Bank Branch of Kubu RokanHilir Districkis aninstitution that was established with the main objective to collect funds from the publicand distribute it to the public in the form of credit. Given credit banks help people inventure capital and other procurement. Problems arising in the provision of credit isnot the return of credit according to the agreement that has been established, with noreturn of the credit or credit problems it will be risky to smooth the business of thebank. Therefore, the provision of credit required in the process of analyzing themaximum credit to avoid a credit crunch. The purpose of this research is to determinethe theloan processing services on a regional Companies Rokan Hilir Rural BankBranch of Kubu RokanHilir Districk. Lending procedures in Local Companies RokanHilir Rural Bank Branch of Kubu RokanHilir Districk starting from the loanapplication by the customer and then Accounts Officer analyze the application and thecompleteness of the existing terms and then conducted a survey of businesses, creditguarantees and credit manager will determine whether or not credit is given. This typeof research is quantitative type, the research emphasizes on the analysis of numerical(numbers) are processed with statistical methods, so as to obtain result of the variables.Methods of collection was done by a list of questions (questionnaire), interviews,observation, and documentation.The operational variables of this research isCharacter,Capital, Capacity, Codition Of Economic, Collateral and Constraints. The results ofthis research to the Character and Capital is good enough, Capacity is good,whileCodition Of Economic and Collateralthe result is good enough, andaboutConstraints the results is good enough. The conclusion of the study showed that theloanprocessing services on a regional Companies Rokan Hilir Rural Bank Branch of KubuRokanHilir Districk is good enough.